Screening for Celiac Disease in Patients with Irritable Bowel Syndrome Fulfilling Rome III Criteria - Al-Abachi, Khaldoon Thanoon (Journal of Coloproctology, 2021)
Background Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder. Celiac disease (CD), a treatable autoimmune enteropathy, with varied presentations, may simulate clinically symptoms of IBS. The aim of the present study is to screen for CD in patients with IBS diagnosed based on the Rome III criteria.Patients and Methods A cross-sectional study was conducted at a secondary care gastrointestinal unit in Al-Salam General Hospital in Mosul city, Iraq, from November 2015 to October 2016. All patients fulfilling the Rome III criteria for IBS were screened for CD using antitissue transglutaminase IgA antibodies (anti-tTG). Patients who tested positive were subjected to endoscopic duodenal biopsy to confirm the diagnosis of CD.Results A total of 100 patients were included in the present study (58 female and 42 male), the mean age of the participants was 40.8 years old (standard deviation [SD] ± 11.57). Ten patients (10/100, 10%) tested positive for anti-tTG antibodies. Five of the seropositive patients (5/10, 50%) showed positive biopsy results according to the Marsh classification, 3 of whom having diarrhea, and 2 with constipation.Conclusion Positive serology and biopsy results suggestive of CD are common among patients with IBS. Screening patients with IBS for CD is justified.
Keywords: irritable bowel syndrome; celiac disease; anti-tTG antibodies; duodenal biopsy